Factors Associated with the Clinical Course of Vitreomacular Traction. (21st December 2020) - Petrou, Petros; Chalkiadaki, Evangelia; Errera, Marie-Helene; Liyanage, Sidath; Wickham, Louisa; Papakonstantinou, Evangelia; Karamaounas, Aristotelis; Kanakis, Menelaos; Georgalas, Ilias; Kandarakis, Stylianos; Charteris, David
Abstract : Background . To analyze the optical coherence tomography (OCT) characteristics as well as the clinical and demographic features to investigate their possible role to the course of vitreomacular traction syndrome. Methods . The inclusion criteria were vitreomacular adhesion with traction causing distortion of the retinal architecture, with or without the presence of an epiretinal membrane, regardless of the size of the adhesion; age >18 years; follow-up of at least three months; and adequate quality OCT scan. Measurements of foveal thickness, average macular thickness, macular volume, maximum vertical and horizontal vitreomacular adhesion, nasal and temporal angles of traction, hyaloid hyperreflectivity, the presence of an epiretinal membrane (ERM), and cone outer segment tips detachment were obtained. Results . 150 eyes were included in the analysis. 36 eyes (24%) developed complete resolution at the last visit, 19 eyes (12.7%) formed a full-thickness macular hole, and 95 eyes (63.3%) showed no resolution of the traction. Better BCVA at the first visit was associated with an increased likelihood of resolution of the VMT, but increasing age, CMT, and BCVA in the end of the follow-up was associated with a reduction in the likelihood of resolving. Of the other variables that were studied, no statistical significant predictors were identified. Conclusions . Better BCVA in the first visit was associated with an increased likelihood of resolution of the VMT that occurred in 24% of our cases. Other factors such as the vertical area of adhesion and the angle of adhesion were not identified as prognostic factors affecting the clinical course of the disease.